Incidence and outcome of transient and permanent atrioventricular heart block after pediatric heart surgery: A retrospective study from Saudi Arabia - Muhammad Shahzad; Yasser Abdulrhman Alheraish; Reem Beheri; Khaled Alarwan; Majid Shahani; Sarosh Waheed; Kashif Rizvi (Journal of Pediatric Critical Care)
Background: Atrioventricular heart block (AVHB) following pediatric cardiac surgery has a remarkable concern in postoperative days, sometimes manifesting a transient event resolving in 14 days. The prevalence of this issue has been evidenced to range from 1% to 4% across multiple studies. This study was conducted to find the incidence and outcome of transient and permanent AVHB after heart surgery in children. Subjects and Methods: A collection of data was made on patients ranging in age from 0 to 15 years old who had heart block. Twelve-lead electrocardiograms were performed every other day following cardiac surgical intensive care unit policy postoperatively. Patient data were originally analyzed by comparing two cohorts: those with permanent AV block and those with transitory AV block. Results: Out of the total of 4920 open heart surgeries, a subset of 146 individuals experienced third-degree AV block for a duration of at least 12 h, representing a prevalence of 2.9%. Within this group, 116 patients exhibited transient AV block, accounting for 2.3% of the total surgeries, while the remaining 30 patients suffered from a permanent form of third-degree AV block, constituting 0.6% of the surgeries. The average duration for the recovery of AV conduction was found to be 6.65 ± 2.8 days. While, weight at time of operation, cardiopulmonary bypass time, and re-intervention at same admission are related with high risk of AVHB. Conclusions: AVHB is a notable complication of pediatric heart surgery. It is associated with low weight, longer bypass times, and redo surgery in the same admission.